Il lungo viaggio verso la notte Based on a Play by Eugene O'Neill - Lumet, Sidney; Kaufman, Boris; Hepburn, Katharine; Richardson, Ralph; Robards, Jason (Sinister Film, 2016)
The Tyrone family is a dysfunctional one not the least of which is the matriarch's (Hepburn) drug addiction. Her ex-Shakespearean actor husband James (Richardson) is a rather insensitive miser who failed to adequately praise his wannabe actor eldest son Jamie (Robards Jr.) such that he's an alcoholic failure. The couple's other son is the disease weakened favorite son Edmund (Stockwell) who struggles to learn his family's secret truths all of which are revealed (e.g. how the family got to where they are now) during the course of this near three hour film. The story is told through a series of scenes much like a play in which each character gets to spend at least some time alone with each other character. There are also scenes featuring each parent and their two sons together. The film begins curiously and outdoors as each of the male characters "walk on egg shells" trying to keep Hepburn's from going on a morphine binge. Of course they fail and the root causes of all the family's members problems come to light one by one. [www.classicfilmguide.com]
Keywords: DVD-Video